LITERATURE REVIEW: THE INFUENCING FACTORS OF EARLY MARRIAGE IN ADOLESCENTS - Handayani, Sri; Kora, Firmina Theresia; Monika, Rika; Rahayu, Amin Dwi (LPPM Sekolah Tinggi Ilmu Kesehatan Yogyakarta, 2022)
Background: Early marriage is a problem arised among teenagers. Early marriage has negative impacts including reproductive health, especially for women, and the impact on adolescent emotions. Objective: to analyze the journals with specific topic to show readers what has been studiedfrom the topic and what has not been researched yet, to look for factors influencing early marriage. Methods: The study used literature review strategy. Results: From the results of the literature review, it was obtained twelve journals related to factors that affect the early marriage in adolescents. There are nineteen factors that influence early marriage, namely: education, knowledge, socio-cultural, parents, social norms, economy, gender, ethnicity, age of respondents, age of menarche, premarital pregnancy, media exposure, attitudes, peer influence, region, number of family members, income, place of residence, and religion. While the factors that do not affect the early marriage are the phenomenon of maturity, fulfillment of romance, work, stigma, poverty, family support. Conclusion:the factors influencing early marriage were education, income, knowledge, economy, family members, social and gender norms, ethnicity, age of respondents, media exposure, parents, culture, age of menarche, attitudes.